The analysis of using TikTok Affiliate for increasing sales of DTF printed t-shirts in Wifiprincess Small Enterprise - Septiawan, Bambang; Nurul Farida; Suprianto; Mufid A; Agus Hermawan; Puji Handayati (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study explores the effectiveness of TikTok Affiliate in enhancing the sales of DTF printed t-shirts at Wifiprincess, a small fashion business in Indonesia. Employing a qualitative approach with a case study design, data were collected through in-depth interviews with the owner, an employee handling affiliate operations, and a customer, alongside participatory observations. The findings reveal that TikTok Affiliate significantly boosts sales through a cyclical process involving affiliate recruitment, negotiation, new product development, content promotion, and order conversions. The process aligns with the AIDA model (Attention, Interest, Desire, Action), where affiliate content captures attention, builds interest, stimulates desire, and drives purchases, while the Elaboration Likelihood Model (ELM) highlights the dominance of the peripheral route in influencing consumer behavior through visual appeal. Key indicators such as authentic content creation, trend responsiveness, and strategic affiliate collaboration were critical to success. Theoretically, this research enriches the application of AIDA and ELM in digital marketing contexts, particularly on short-video platforms. Practically, it offers actionable insights for small businesses to leverage TikTok Affiliate for cost-effective market expansion, emphasizing the importance of authenticity and cultural relevance in content strategies.